REGULATORY RESTRICTIONS AND EXPORT OPPORTUNITIES AGRICULTURAL PRODUCTS WITHIN THE FRAMEWORK OF THE EAEU (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines the key legal barriers and institutional constraints hindering the effective export of agricultural products within the framework of the Eurasian Economic Union (EAEU). A comparative analysis of differences in the national legislation of EAEU member states—Armenia, Belarus, Kazakhstan, Kyrgyzstan, and Russia—is conducted. Particular attention is paid to sanitary and phytosanitary measures, technical regulations, certification procedures, and the level of digital document circulation. Successful cooperation cases are analyzed, and practical recommendations are offered to reduce export barriers and strengthen legal integration of the agricultural markets across EAEU countries. The study is based on legal acts, statistical reports, and data from the Eurasian Economic Commission.
Keywords: EAEU, agriculture, export, legal regulation, sanitary standards, technical regulations, digitalization, agricultural market, trade barriers, harmonization.